2023
DOI: 10.1001/jamanetworkopen.2023.24389
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Social Media Use, Mental Health, and Gender Identity Among US Youths

Sarah M. Coyne,
Emily Weinstein,
J. Andan Sheppard
et al.

Abstract: ImportanceMental health among children and adolescents is a critical public health issue, and transgender and gender nonbinary youths are at an even greater risk. Social media has been consistently associated with youth mental health, but little is known about how gender identity interacts with this association.ObjectiveTo use a risk and resilience approach to examine the association between social media use and mental health among transgender, gender nonbinary, and cisgender youths.Design, Setting, and Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Online communities can particularly benefit those who experience greater barriers accessing supports and services (e.g., rural and remote communities, marginalized groups), experience social anxiety, or are concerned about being stigmatized [34,35]. For instance, research suggests that people who identify as LGBTQ2S+ experience greater mental health benefits from active social media use compared to cisgendered people as it provides them an outlet for self-expression and access to social support they may not have access to offline [36,37]. Participants from our study mainly identified as LGBTQ2S+ (57%) and also expressed how TikTok helped them find communities they could relate to.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online communities can particularly benefit those who experience greater barriers accessing supports and services (e.g., rural and remote communities, marginalized groups), experience social anxiety, or are concerned about being stigmatized [34,35]. For instance, research suggests that people who identify as LGBTQ2S+ experience greater mental health benefits from active social media use compared to cisgendered people as it provides them an outlet for self-expression and access to social support they may not have access to offline [36,37]. Participants from our study mainly identified as LGBTQ2S+ (57%) and also expressed how TikTok helped them find communities they could relate to.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our findings represent the experiences of youth who mainly identified as white and women. Having a more ethnic-and gender-diverse sample could have provided further insights on youths' use of TikTok for mental health information as minority populations experience different access to mental health care and support compared to white, cis-gendered individuals [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in the social sciences are increasingly conducting focus groups, not for data collection but rather data clarification, where they co-interpret results with those having lived experience. These insider perspectives provide possible explanations for results not previously thought of and give greater direction, clarity, and insight to researchers and empower respondents (see Coyne et al, 2023;Dodson et al, 2007;Weinstein & James, 2022). Focus groups can be done with all racial groups but should especially be considered when researchers have a different racial identity than participants.…”
Section: Post-hoc Focus Groups With Participants and Community-based ...mentioning
confidence: 98%
“…Eskandari et al (2020), discovered that social support (r=0.84, P<0.0001), media literacy (r=0.698, P<0.0001), and emotional intelligence (r=0.798, P<0.0001) were all significantly correlated with network addiction virtual social. Meanwhile, mental health among children and adolescents is a critical public health issue which adolescents are at greater risk (Coyne et al, 2023); and social media are consistently linked to adolescent mental health (Anthonysamy et al, 2022).…”
Section: Social Media Information Literacy (Smil) and Emotional Intel...mentioning
confidence: 99%